Corporate Criminal Liability under Indonesia’s New Criminal Code: A Normative and Implementation-Based Approach - Laila Uswatun Chasanah; Kahfi Arif Suryadi; Hendi Budiaman; Fadhil Muhammad; A. Rachmat Wirawan (JURNAL MAHASISWA YUSTISI, 2026)
Corporate criminal liability has become increasingly significant in Indonesia following the enactment of Law No. 1 of 2023 on the Criminal Code, which formally recognizes corporations as subjects of criminal law and establishes a more comprehensive framework for attributing criminal responsibility to corporate entities. This study aims to analyze the normative construction of corporate criminal liability under the new Criminal Code and examine its potential implementation within Indonesia’s criminal justice system. This research employs a normative juridical method using statutory and conceptual approaches, with primary and secondary legal materials analyzed qualitatively. The results demonstrate that the new Criminal Code strengthens the legal foundation for corporate criminal liability by regulating the conditions for attributing criminal acts to corporations, identifying parties who may bear responsibility, and providing corporate-specific sanctions. Nevertheless, its implementation may encounter challenges concerning attribution of fault, identification of responsible corporate actors, evidentiary standards, and consistency among law enforcement authorities. The study concludes that effective corporate criminal liability requires coherent judicial interpretation, clear enforcement guidelines, and strengthened institutional capacity to ensure legal certainty, proportionality, and effective deterrence of corporate crime.